(Re)performing scenography: Josef Svoboda as a tutor. Issue 3 (2nd July 2020) - Pantouvaki, Sofia
ABSTRACT: The document presented here was part of the curriculum offered in 1997 by the Department of Stage Design of the Theatre Faculty (DAMU) in Prague to the international exchange students from the Master of Arts in European Scenography at Central Saint Martins College of Art and Design (London, UK) and the University of the Arts in Utrecht (Netherlands). It is based on two lecture-presentations by Josef Svoboda delivered at DAMU on 15 January and 22 January 1997, offering a rare opportunity for early-career designers to discuss scenography in detail and in context with him. The lectures provided a flowing narrative as a presentation and a sharing of Svoboda's design experiences; they included scenographic work presented by the designer himself with detailed descriptions and their technical solutions. This document is an edited selection of excerpts from the lectures accompanied by editorial commentary. The content of the discussion provides not only a vivid document of Svoboda's personal trajectory, but also a historical record of twentieth-century stage technologies and collaboration on an international scale. Given that Josef Svoboda's pedagogical involvement is rarely discussed, this document aims to contribute to Svoboda's legacy by bringing to light this lesser-known side of the great designer.